1977
DOI: 10.1128/jb.131.2.431-437.1977
|View full text |Cite
|
Sign up to set email alerts
|

Induction of alkaline phosphatase in Escherichia coli: effect of procaine hydrochloride

Abstract: The effect of procaine hydrochloride, an anesthetic known to alter membrane structure, on the induced formation of alkaline phosphatase, a periplasmic enzyme, in Escherichia coli was investigated. Procaine hydrochloride specifically arrested the appearance of active alkaline phosphatase while permitting the induction of another enzyme, beta-galactosidase, which is internally localized. Evidence has been obtained to show that procaine hydrochloride does not arrest synthesis of inactive monomer subunits of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Therefore, short-term treatment with procaine has no effect on the maturation of the majority of periplasmic components. In the case of alkaline phosphatase, procaine addition to phosphate-starved cells blocked the appearance of the enzyme activity (28). We have confirmed that observation in our strains (data not shown).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, short-term treatment with procaine has no effect on the maturation of the majority of periplasmic components. In the case of alkaline phosphatase, procaine addition to phosphate-starved cells blocked the appearance of the enzyme activity (28). We have confirmed that observation in our strains (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Procaine, a local anesthetic, is a membrane-active drug (18). It has been reported that 20 mM procaine does not inhibit either overall protein synthesis or induction of /3-galactosidase (28). Therefore, any effect on the growth rate of cells in the presence of 20 mM procaine and a particular carbon source might reflect action of the drug on the entry of carbohydrate into the cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of wild-type strains with the local anesthetic procaine mimics envZ missense mutations. Procaine causes a PhoA-MalE-LamB-OmpFphenotype by blocking transcription of these genes (5,6,19,25). Missense mutants resistant to procaine action map in envZ (24).…”
mentioning
confidence: 99%
“…The administration of sub-lethal concentrations of procaine to E. coli causes pleiotropic alterations in the synthesis of a wide variety of outer membrane and periplasmic proteins [6][7][8][9][10]. We were interested in establishing whether sub-lethal concentrations of procaine would interfere with the stable maintenance of pSC101 by inhibiting the synthesis of a chromosomally encoded membrane protein required for par function.…”
Section: Introductionmentioning
confidence: 99%